Cecal microbiome transplantation without antibiotic preconditioning standardizes murine microbiomes - Howard-Stone, Rye; Gerwin, Philip; Capunitan, Darien; Driscoll, Mark; Jackson, Eric; Tran, Thi Dong Binh; Măndoiu, Ion; Oziolor, Elias (Frontiers in Microbiology, 2025)
IntroductionTranslation of nonclinical findings from laboratory mice to the clinic may be confounded by un-controlled variance in bacterial gut content, as a driver of immune maturation and recruitment, as well as drug metabolism. Understanding and controlling for microbiome variation in animal experiments can lead to better reproducibility of animal findings, more translatable characterization of efficacy and toxicity end-points and time and cost savings associated with pharmaceutical development. Microbiome composition has been linked to failure of translation of drug responses.MethodsIn an effort to test the stability of microbiome introduction, we compare various methods for establishing a well-characterized, stable bacterial community in laboratory mice via Cecal Microbiome Transplant (CMT) with and without antibiotic preconditioning.ResultsWe demonstrate a single CMT treatment protocol effectively treats outbred mouse populations with two different initial gut bacterial profiles, causing the populations to converge to a third, more wild-type bacterial genetic environment suitable for initiation of nonclinical studies. We show that ASV-based monitoring provides the highest resolution for identifying and tracking bacterial profile differences, which can be obscured at the species level. We find that antibiotic preconditioning reduces efficiency for uptake of CMT-specific strains. Instead, antibiotics introduce uncontrolled variance in the resulting microbiome composition.ConclusionsWe propose that CMT without antibiotic preconditioning provides increased control over host microbial composition, enabling expanded utility, accuracy, and relevance for nonclinical drug toxicity and therapeutic effect studies in laboratory mice, with minimal additional costs.